An Alkene-Forming Cascade Reaction En Route to 2,2'-Bi(glycerol) - Li, Xiaoxun; Livant, Peter D.; Chen, Jianjun (Synlett, 2018)
Synthesis of 2,3-bis(hydroxymethyl)butane-1,2,3,4-tetraol is of great interest because of its utility as a potential precursor to new dendrimers, in the preparation of unnatural lipids, and in the synthesis of open-framework coordination polymers. Synthesis of this new six-hydroxyl compound is achieved in four steps from commercially available starting materials. In this process, a new olefin-forming cascade reaction was discovered.
Keywords: cascade reaction; alkenes; olefins; 2,2'-bi(glycerol); hexaalcohol